ORAL HEALTH AND VITAMIN D IN ADULT: SYSTEMATIC REVIEW - Novitarina, Elysabet (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The role of nutrition in oral diseases has grown in popularity, and recent studies have revealed increasingly important links between nutritional deficiencies and oral pathologies. The levels of vitamin D (VD) have recently garnered an increasing amount of focus in the realm of oral health. VD deficit (VDD) is related with a wide array of oral health issues during growth and maturity; decreased VD synthesis may speed up the progression of some of these conditions. In children, severe VDD can produce faulty tooth mineralization, which can result in problems in both the dentin and the enamel. As a direct result of this, there is a potential for an increased risk of the beginning stages of dental caries as well as their advancement. In addition, VDD has been linked to a higher prevalence of periodontitis and gingival inflammation, and a number of recent research, both preclinical and clinical, have uncovered putative routes through which vitamin D may interact with the periodontium. The correction of VDD by supplementation may be one factor that contributes to the successful treatment of periodontitis; nevertheless, alveolar bone regeneration treatments conducted in individuals with baseline VDD appear to be more likely to fail. Some forms of oral cancer and osteonecrosis of the jaw may be connected to vitamin D, as may certain oral malignancies. This study seeks to present thorough evidence of how VD levels should be evaluated to maintain excellent oral health, as well as to describe how VDD may hinder oral development and its function in particular oral disorders.